UJI EFEKTIVITAS PUPUK ORGANIK PADAT PADA PERTUMBUHAN DAN PRODUKTIVITAS LIMA VARIETAS LOKAL TANAMAN TERONG (Solanum Melongena L.) - Satria Wisada Kusumadiharja; Usmadi Usmadi (Berkala Ilmiah Pertanian, 2020)
Eggplant is a plant that requires appropriate organic fertilization to produce quality fruit. Research on the effect of applying solid organic fertilizer on growth and the level of productivity of local eggplants is the main focus, especially related to growth and yield. The purpose of this study was to determine the growth and productivity of local eggplants against the provision of solid organic fertilizer carried out in paddy fields in Jember. The method used is a completely randomized design (CRD) of two factors, the first factor is the variety factor with 5 levels while the second factor is the factor of solid organic fertilizer consisting of 4 treatment levels so that there are 20 treatment combinations. Each treatment was repeated 3 times, so that there were 60 experimental unit units and each experiment unit consisted of 4 plants. The first factor is pruning with 5 levels including V1: eggplant Phiton, V2: Demak Ijo eggplant, V3: Bonar eggplant, V4: Rondha eggplant and V5: Inayah eggplant. The second factor is the treatment of solid organic fertilizer using 4 levels including P0: without solid organic fertilizer, P1: compost, P2: animal dung (kohe) goat, P3: cow kohe. The results showed that the interaction between eggplants with the trade name Inayah (V5) with the treatment of organic solid fertilizer for cow dung (P3) had optimal number of branches, productive interest and fruit weight. Local varieties of eggplants with the trade name Inayah (V5) have an optimal effect on plant height, number of leaves and productive fruit. The treatment of cow manure (P3) solid organic fertilizer has an optimal effect on plant height and productive fruit. Keywords: Germplasm, Local Eggplant, Organic Fertilizer.